Analisis Text Mining Klasifikasi Kegiatan Keluarga menggunakan Orange dengan Metode Naive Bayes - Arsya Fathiarahma; Apriade Voutama; Taufik Ridwan; Nono Heryana (LPPM STT Terpadu Nurul Fikri, 2023)
The dual roles performed by women often lead to conflict in the family. Disputes can occur due to the lack of family roles in helping balance the work at home and office experienced by career women and mothers. The Naïve Bayes algorithm is used in this study to determine the results of applying the Naïve Bayes algorithm classification based on role, activity, age, and interest in a family. A total of 287 data records generated from the survey were used in this study and a data split of 80:20 for training and testing data using orange data mining tools. The results show that the calculation accuracy with the Naïve Bayes algorithm reaches 93%, with the conclusion that the use of orange data mining tools results in good accuracy.